DIAGNOSIS AND TREATMENT OF PATIENTS WITH CRYOPYRIN-ASSOCIATED PERIODIC SYNDROME - A. L. Kozlova; B. S. Pershin; T. V. Varlamova; A. Yu. Shcherbina (Вопросы современной педиатрии)
Cryopyrin-Associated Periodic Syndrome (CAPS) refers to a group of autoinflammatory diseases and is caused by autosomal dominant mutations of the NLRP3 gene coding. Relapsing fever, rash, laboratory changes and inflammatory lesions of various organs are typical manifestations of CAPS. Inhibitors of interleukin 1, including canakinumab, are modern means of pathogenetic therapy of patients with CAPS. The article presents the treatment results in 5 pediatric patients with CAPS. Application of canakinumab led to the relief of all major symptoms (fever, inflammatory changes in the blood lymphoproliferation, signs of organ damage), and no relevant side effects was detected.